DEVELOPING INTERNAL MEDIA REGULATION FOR LOCAL MEDIA BASED ON COMMUNITY - Sunarto Sunarto; Adi Nugroho; Amida Yusriana (al-Balagh : Jurnal Dakwah dan Komunikasi, 2020)
A serving community is a strategic plan that needs to be considered by several local newspaper production in Java. This includes a newspaper in Semarang, Suara Merdeka Daily. This study determines the commitment of Suara Merdeka Daily in serving the community. Data were obtained from the analysis of internal regulatory content on editorial work and business. This study used Focus Group Discussions (FGD) to support and share data with the newspaper management team. The results showed that the editorial's internal regulations did not explicitly indicate the commitment to serve the community. This regulation has been implemented for a long time, yet it does not adjust to the relevant newspapers' actual conditions. Generally, businesses have rules that require community involvement in their programs. The management team is expected to revise the regulations to suit the public's needs and develop relevant community involvement for the local newspaper's existence.